2017
DOI: 10.1089/ten.tea.2016.0525
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-183-5p Increases with Age in Bone-Derived Extracellular Vesicles, Suppresses Bone Marrow Stromal (Stem) Cell Proliferation, and Induces Stem Cell Senescence

Abstract: Microvesicle- and exosome-mediated transport of microRNAs (miRNAs) represents a novel cellular and molecular pathway for cell-cell communication. In this study, we tested the hypothesis that these extracellular vesicles (EVs) and their miRNAs might change with age, contributing to age-related stem cell dysfunction. EVs were isolated from the bone marrow interstitial fluid (supernatant) of young (3-4 months) and aged (24-28 months) mice to determine whether the size, concentration, and miRNA profile of EVs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 52 publications
8
140
0
Order By: Relevance
“…In general, EVs carry and transfer a wide variety of molecules, such as micro RNAs (miRNAs), messenger RNAs, DNA, and proteins. Remarkably, EVs secreted from senescent cells have unique characteristics and contribute to regulate the behavior of recipient cells similarly to soluble SASP factors . By analyzing EVs from senescent human dermal fibroblasts, Terlecki‐Zaniewicz and colleagues have identified a set of selectively retained or secreted miRNAs and have shown that senescent cell‐derived EVs with their miRNA cargo contribute to an antiapoptotic environment in tissues where senescent cells accumulate .…”
Section: Evs As a Key Component Of Sasp Modulate Nk Cell Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, EVs carry and transfer a wide variety of molecules, such as micro RNAs (miRNAs), messenger RNAs, DNA, and proteins. Remarkably, EVs secreted from senescent cells have unique characteristics and contribute to regulate the behavior of recipient cells similarly to soluble SASP factors . By analyzing EVs from senescent human dermal fibroblasts, Terlecki‐Zaniewicz and colleagues have identified a set of selectively retained or secreted miRNAs and have shown that senescent cell‐derived EVs with their miRNA cargo contribute to an antiapoptotic environment in tissues where senescent cells accumulate .…”
Section: Evs As a Key Component Of Sasp Modulate Nk Cell Functionsmentioning
confidence: 99%
“…Remarkably, EVs secreted from senescent cells have unique characteristics and contribute to regulate the behavior of recipient cells similarly to soluble SASP factors. 56,57 By analyzing EVs from senescent human dermal fibroblasts, Terlecki-Zaniewicz and colleagues have identified a set of selectively retained or secreted miRNAs and have shown that senescent cell-derived EVs with their miRNA cargo contribute to an antiapoptotic environment in tissues where senescent cells accumulate. 58 Furthermore, ovarian cancer-derived exosomes expressing miRNA-433 have the potential to modulate the tumor microenvironment by inducing cellular senescence in neighboring cells.…”
Section: Evs As a Key Component Of Sasp Modulate Nk Cell Functionsmentioning
confidence: 99%
“…Plasma EVs isolated from young but not from elderly donors promote the osteogenic differentiation of mesenchymal stem cells in a galectin-3 dependent manner 18 . Furthermore, EVs purified from the elderly suppress cell proliferation and osteogenic differentiation of bone marrow stromal cells 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In our infection system, despite the repressed protein levels, we find Hmox-1 mRNA to be up-regulated in macrophages infected with L. donovani . The negative correlation between Hmox-1 RNA and protein levels, amongst other factors, could be due to increased secretion of Hmox-1 in the culture medium, as Hmox-1 can be a secreted protein [86].…”
Section: Resultsmentioning
confidence: 99%